Sudden death among us (Conclusion) - Quesada, Fortunato (1920)
The most common cause of sudden death among us is alcoholism. His death is the dominant mechanism of pulmonary congestion. The time of year when most deaths occur in this class is the months of May and June, here are for the late fall and early winter, which agrees with the above finding. After alcoholic lung congestion, cases of cardiorenal brighticos asystolic and hemorrhagic malarial esplenomegálicos abound. Going up the mechanism of all cases entered, you get to always find, as ultimately, the functional failure of one of the three main vital organs: the brain, heart and lungs; because it ends up brain or cardiac syncope or asphyxia. There is a huge preference of this kind of death for males. In The most favored ages are: 40 to 49 and from 60 to 69 years. Indians and mestizos are the most targeted. It marked the abundance with which it comes in solteror individuals. Most of our observations have emanated from the workers.